THE INFLUENCE OF TAX UNDERSTANDING AND TAX SANCTIONS ON LAMPUNG MICRO, SMALL AND MEDIUM ENTERPRISES (MSMEs) TAXPAYER COMPLIANCE - Ega Zulkarnain; Ratna Septiyanti (ITB AAS Indonesia Surakarta, 2024)
This study aims to analyze the understanding of taxes and tax sanctions on the taxpayer compliance of MSMEs Lampung. The sample used in this research is 57 taxpayer respondents who are registered with DJP Bengkulu Lampung. The sampling technique used in this study is simple random sampling. The type of data used is primary data. This type of research is quantitative research with data collection techniques, namely the method of distributing questionnaires to Lampung MSMEs taxpayers. The data analysis technique in this study was carried out using the SmartPLS version 4.0 software program method. The results of this study indicate that tax understanding and tax sanctions have a positive and significant effect on Lampung MSMEs taxpayer compliance. Keywords: Taxpayer Compliance, Tax Understanding, Tax Sanctions.